2011
DOI: 10.1038/pr.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

Increased MMP-9 and TIMP-1 in mouse neonatal brain and plasma and in human neonatal plasma after hypoxia–ischemia: a potential marker of neonatal encephalopathy

Abstract: ArticlesTranslational Investigation nature publishing group INTRODUCTION:To implement neuroprotective strategies in newborns, sensitive and specific biomarkers are needed for identifying those who are at risk for brain damage. We evaluated the effectiveness of matrix metalloproteinases (MMPs) and their naturally occurring tissue inhibitors of metalloproteinases (TIMPs) in predicting neonatal encephalopathy (Ne) damage in newborns. RESULTS: Plasma MMP-9 and TIMP-1 levels were upregulated as early as 1 h after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 30 publications
(43 reference statements)
8
31
0
19
Order By: Relevance
“…This spatiotemporal pattern of MMP-9 upregulation strongly correlated with the period of highest delayed neuronal death in the correspondent animal model [10]. Recent studies by Bednarek et al [11] using a mouse model of neonatal HI injury have demonstrated a significant increase in the levels of neocortical gelatinolytic activity and protein levels of MMP-9 but not MMP-2 24 h and 3 days after hypoxic ischaemia. Given these findings, we therefore conclude that MMP-9 may be a useful target for rescue therapies in the injured developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…This spatiotemporal pattern of MMP-9 upregulation strongly correlated with the period of highest delayed neuronal death in the correspondent animal model [10]. Recent studies by Bednarek et al [11] using a mouse model of neonatal HI injury have demonstrated a significant increase in the levels of neocortical gelatinolytic activity and protein levels of MMP-9 but not MMP-2 24 h and 3 days after hypoxic ischaemia. Given these findings, we therefore conclude that MMP-9 may be a useful target for rescue therapies in the injured developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in TIMP1 appears to be compensatory to increased MMP9. Consistent with our findings, increased MMP9 and TIMP1 occurs in pathologies such as neonatal encephalopathy [166] and aortic aneurysm [167]. Our results demonstrated that Aza treatment reduces collagen deposition and also decreases MMP9 and TIMP1 expression in HHcy.…”
Section: Global Dna Methylation In Hyperhomocysteinemiasupporting
confidence: 80%
“…We visualized the signals using enhanced chemiluminescence (ECL Prime; GE Healthcare Bio-Sciences, Pittsburgh, PA, USA) before exposure to autoradiographic film (Phenix, Candler, NC, USA). We detected pro-MMP-2, cleaved-MMP-2, MMP-8, MMP-13, TIMP-1, TIMP-2, TIMP-3, TIMP-4, β-actin, and vinculin bands at 72,64,53,54,26,24,26,25,42, and 117 kDa, respectively. Omission of the primary antibodies eliminated the chemiluminescent signals, thereby establishing the specificity of the primary antibodies to detect the specific protein bands.…”
Section: Western Immunoblotmentioning
confidence: 99%
“…Consequently, it is important to understand the effects of different durations of reperfusion after ischemia on brain injury to determine therapeutic strategies that could attenuate the untoward effects of perinatal brain damage [24]. Accumulating evidence suggests that there is an association between BBB dysfunction and changes in MMPs and TIMPs after hypoxic-ischemic brain injury in the neonatal rodent brain [13,25,26]. However, the expression profiles of MMPs and TIMPs have not previously been examined after ischemia in the brain of a large mammalian fetus.…”
Section: Introductionmentioning
confidence: 99%